2019
DOI: 10.4236/as.2019.107066
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Seed and Tuber Production Potential in Varieties of <i>Sphenostylis stenocarpa</i> (Africa Yam Bean)

Abstract: Twenty accessions of African Yam Bean, grown at the Teaching and Research Farm of Ladoke Akintola University of Technology, Ogbomoso during the cropping seasons of May to November, 2014 and 2015 were assessed for genetic diversity and Genotype × Environment interaction effects on trait performance and their ability to produce tuber. The first six Principal Components jointly explained 70.30% of the total variation among the accessions. Vine length, branching pattern, pod number, pod length, seed number, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…The greater magnitudes of PCV, environmental variance and the variance due to accession × environment interaction compared to the GCV and genotypic variance suggested higher environmental influence in the expression of all traits. Similar results have been reported by [32,35,38,39] in their studies of AYB variability. The high PCV and moderate GCV observed for both SYPPL and NPPPL indicated the presence of considerable variation for these traits among the AYB accessions studied, and thus provides opportunity for improvement through effective selection.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The greater magnitudes of PCV, environmental variance and the variance due to accession × environment interaction compared to the GCV and genotypic variance suggested higher environmental influence in the expression of all traits. Similar results have been reported by [32,35,38,39] in their studies of AYB variability. The high PCV and moderate GCV observed for both SYPPL and NPPPL indicated the presence of considerable variation for these traits among the AYB accessions studied, and thus provides opportunity for improvement through effective selection.…”
Section: Discussionsupporting
confidence: 92%
“…The significant differences observed among the accessions for all traits was an indication of the genetically diverse nature of the germplasm and suggested that good progress can be made in the improvement of desired traits. Previous studies using fewer number of accessions [2,[14][15][16][32][33][34][35][36] had reported substantial variability for different traits in African yam bean. The significance of environment and accession × environment interaction effects for all traits indicated that the performance of accessions were influenced by environment, and the relative rank in performance of accessions varied with the different environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Parvez [17], ear weight, ear diameter and ear length are important characters that influence yield efficiency in maize, while tassel branches, length and weight are important tassel characters that affects yield efficiency, as they determine the abundance or otherwise of pollen grain produced by the maize plant. Findings of the research agrees with the initial assertions of Gue et al [18]; Ibirinde et al [19], that tassel traits affect grain yield either physiologically; by competing for photosynthesis, or physically by shading effect. Thus, an ideal male parent for maize breeding programme should have numerous tassels that are capable of producing large amount of pollen grains, whereas an ideal female should partition more towards big ear and hence should possess small tassel [20][21][22].…”
Section: Agronomic Traits Of Maize Genotypessupporting
confidence: 91%
“…Cassia hirsuta L. has equally been reported to contain high protein, lipid, potassium, fiber, carbohydrates, and energy contents (34), while velvet bean (Mucuna pruriens) has been reported to have optimum crude protein, lipid, fiber, carbohydrate, energy, calcium, potassium, phosphorus, zinc, manganese and magnesium content which is capable of supplying human nutritional needs (35). Examples of other underutilized legumes and nutrient composition are listed in Table 1 below: Some underutilized legumes have multiple edible parts; for instance, different parts of winged bean which include the flower, seeds, pod case, immature pods, tuberous roots, and leaves (62), similarly, the seeds and leaves of fenugreek are edible (63), also, marama bean produces edible grains and tubers beneath their root (49), zombie pie produces edible seeds and tubers (16) and African yam bean produces edible tubers and seeds (64). The edibility of multiple parts of underutilized legumes gives a chance for the human nutritional requirements to be satisfied through different diets, especially for picky eaters, making it…”
Section: Nutritional Status Of Underutilized Legumesmentioning
confidence: 99%